URGENSITAS HARMONISASI HUKUM PERLINDUNGAN DAN PENGELOLAAN HUTAN DALAM MITIGASI PERUBAHAN IKLIM GLOBAL MELALUI PROGRAM REDUCING EMMISION DEFORESTATION AND FOREST DEGRADATION AND ENHANCING STOK CARBON - Gunawati, Dewi (Yustisia, 2015)
AbstrakThis study aims to identify the urgency or the reasons for the harmonization of legal protection and management of forests in mitigating global climate change through REDD + .Urgency harmonize the protection and management of forests in mitigating global climate change examined in three approaches. First, a philosophical approach that formed in the Welfare State Theory by Espring Enderson, active role of the state in the context of the protection and management of forests is that the state is obliged to undertake the protection and management of forests in mitigating global climate change. Studied from the theory of sustainable development Edith Brown Weiss, i) The phenomenon of global climate change is a result of lifestyle or human behavior in the form of patterns of production and patterns of excessive and unfriendly environment. Excessive fossil energy resulting ecological crisis impact on global warming so trigger global climate change. ii) Due to the interest of developing countries to emission concept promoted in the global climate change convention, which it does not restrict their movement from space to improve economic competitiveness by building centers of industrial activity which tends to be a major contributor to the increase in gas emissions greenhouse. In this condition the developing countries try to hum with the concept that those countries have the same right to do the construction. Studied from the theory of justice, John Rawls justice is understood as a balance between personal interests and common interests. In the structure of the society in which justice as the main problems then need to be formulated and given a list of reasons on the principles that must be met by a basic structure of a just society in which the principles of justice must distribute the prospect of meeting the basic needs.Secondly, the juridical approach imprinted on the legal system theory, Lawrence Friedman, and Third, Sociological Approach, engraved on Theory Brianz Tamanaha.